Development of a College Life Adaptation Program for Freshman Student-Athletes - Sang-hyun Kwon (Korea Institute of Sport Science, 2021)
Purpose The purpose of this study was to develop an effective college life adaptation program for freshman student-athletes. Methods A total of 160 student-athletes and 5 experts agreed to participate in this study. Four procedures were followed in this study: the needs assessment, the preliminary program development, and the application of the program. For the needs assessment, in-depth interviews were conducted, and the data were analyzed using an inductive reasoning process. Results The results of the needs investigation showed seven need factors and four interruption factors for college life adaptation. In addition, three need factors based on experience and seven interruption factors based on experience were found. The preliminary program was developed based on the needs assessment through the expert meeting, and the program consisted of four stages. Each stage consisted of three sessions, and each session contained a specific topic. The program was provided to nine freshman student-athletes in two months. As a result, the final program which consisted of four stages and thirteen sessions was developed after the reinforcement process based on evaluation of the preliminary program was conducted. Conclusions It is concluded that, the program is able to be expected to help them to understand their roles, have a better sense of responsibility and improve their self-esteem. Therefore, coaches and mental performance consultants should provide the college life adaptation program for freshman student-athletes to reduce their stress and have a better college life.